Pengaruh POC dan Ragam Pemangkasan Cabang Lateral terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.): Pengaruh POC dan Ragam Pemangkasan Cabang Lateral - Yutri Theresia Yustriana Uskenat; Asep Ikhsan Gumelar; Krisantus Tri P Raharjo (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2026)
This study aimed to determine the effect of liquid organic fertilizer and various lateral branch pruning treatments on the growth and yield of cucumber (Cucumis sativus L.). The research was conducted from January to April 2025 at the experimental field of the Faculty of Agriculture, Universitas Timor. A factorial Completely Randomized Design was used with two factors arranged in a 4 × 4 design and repeated three times, resulting in 48 experimental units. The first factor was liquid organic fertilizer derived from rice washing water, consisting of no treatment, 150 mL/L, 250 mL/L, and 350 mL/L. The second factor was lateral branch pruning, consisting of no pruning, pruning branches 1–6 at 35 days after planting, pruning branches 7–12 at 35 days after planting, and pruning branches 7–12 at 42 days after planting. The treatment combinations were expected to influence vegetative growth and yield components of cucumber. The results indicate that appropriate doses of liquid organic fertilizer and pruning management can support better cucumber growth and productivity.